2006
DOI: 10.1111/j.1471-8286.2006.01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellite loci in Brachyderes rugatus, the Canary Islands pine weevil (Coleoptera: Curculionidae)

Abstract: The Canary Island pine weevil Brachyderes rugatus (Wollaston) consists of four allopatric subspecies that are thought to have arisen from several historic colonization events within the archipelago. We have isolated and optimized seven microsatellite loci from Brachyderes rugatus calvus from Gran Canaria. Six of these loci are polymorphic within B. rugatus (11-22 alleles per locus; heterozygosity between 0.43 and 0.84). There is no evidence for heterozygote deficit within populations or for linkage disequilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Little is known about the population structure of this species. Microsatellites, although widely used for study of populations of other important weevil pests (Dhuyvetter et al, 2002;Ernst et al, 2005;Forgie et al, 2006;Kim and Sappington, 2004;Liewlaksaneeyanawin et al, 2001), have not been reported for this species or any congeners prior to our study (Li et al, 2008). We herein report five primer pairs for microsatellites discovered in GSSW collected from four locations (IA, MT, NM, OR).…”
Section: Characterization Of Microsatellite Loci Inmentioning
confidence: 82%
See 1 more Smart Citation
“…Little is known about the population structure of this species. Microsatellites, although widely used for study of populations of other important weevil pests (Dhuyvetter et al, 2002;Ernst et al, 2005;Forgie et al, 2006;Kim and Sappington, 2004;Liewlaksaneeyanawin et al, 2001), have not been reported for this species or any congeners prior to our study (Li et al, 2008). We herein report five primer pairs for microsatellites discovered in GSSW collected from four locations (IA, MT, NM, OR).…”
Section: Characterization Of Microsatellite Loci Inmentioning
confidence: 82%
“…Microsatellite loci were isolated using a biotin-enrichment protocol based on Forgie et al (2006) and Schemerhorn et al (2003). Whole genomic DNA was extracted from 20 gray sunflower seed weevil specimens using Qiagen's DNeasy Tissue Extraction Kit and was digested with Sau3AI restriction enzyme and ligated to the Sau3AI-specific adaptor by annealing together oligo A and oligo B (Louie and Bardeleben, 2006;Refseth et al, 1997).…”
Section: Methodsmentioning
confidence: 99%